A social history of the Ise shrines : divine capital - Teeuwen, Mark; Breen, John, 1956- (Bloomsbury Shinto studies, 2017)
"Traces the history of the Ise shrines from the 7th century until today, focusing on the many episodes of crisis that transformed the social landscape around the shrines"--